A importância da formação de professores da rede pública de ensino quanto ao uso das tecnologias digitais em suas práticas pedagógicas - um estudo de caso - Ribeiro, Andrea Maria da Fonseca (Universidade Federal Rural do Semi-Árido, 2020)
This work aims to reflect on the importance of training public school teachers on the use of digital technologies in their pedagogical practices, with the objective of investigating whether the practice and use of these digital technological tools are effective in the classroom. class. Based on the experiences, as a student of the undergraduate course in Computer Science and a scholarship holder for the Program of Initiation to Teaching-PIBID and Pedagogical Residence, we share, when planning with teachers, the difficulties of using and accessing technological innovations applied to education, in general, making the need for teacher training visible in the use and applications of digital tools in the respective pedagogical actions. It is a case study that emerged from the perspective of the practices and training paths of these teachers, in the absence of attributions for the use of Information and Communication Technologies (ICTs), in the teaching-learning process. The chosen space was a public school in the Central Potiguar region of the municipality of Santana do Matos. For data collection, previously tested questionnaires were used as a research instrument, mostly composed of objective questions, shared with school teachers to obtain the corpus. Also, with these questionnaires, information was collected on the pedagogical practices of these professionals in order to obtain the largest number of data that can prove the importance of the use of ICTs in the school space. The study was guided by the theoretical contributions of Moran (2000), Kenski (2007), Oliveira (2007), Valente (1999) and other authors who discuss the treatment of information and communication as bias in education. Based on the perception of the aforementioned authors, it is possible to infer that technologies bring necessary contributions to the educational process, they only need to be understood and incorporated pedagogically. After the description and analysis of the data, we were able to conclude that part of the school teachers intend to insert the technological resources in a way that allows the students' learning, along with the curricular components. However, still, there are professionals who face difficulties in the use of these technological tools combined with their pedagogical practice and others who resist the use of any virtual and digital strategies in this process. Teaching with ICTs will only become effective and productive if it springs from the needs of the subjects that make up this process.
Monografia
Keywords: Formação de professor; Prática pedagógica; Tecnologia digital; Inovação tecnológica; Teacher training; Pedagogical practice; Digital technology; Technological innovation; CIENCIAS EXATAS E DA TERRA::COMPUTACAO E INFORMATICA